DEVELOPMENT AND VALIDATION OF METHODS USING DERIVATIVE SPECTRO-PHOTOMETRY FOR DETERMINATION OF DIPYRONE IN PHARMACEUTICAL FORMULATIONS - Costa Lopes, Francisco das Chagas da; Fonseca, Lorenna; Moita, Graziella Ciaramella; Moura Ribeiro, Marcos Vinicius de [UNESP] (Int Journal Pharmaceutical Sciences & Research, 2018)
Dipyrone (sodium noramidopyrine methanesulfate), a member of the pyrazolone group, is a drug that possesses analgesic, antipyretic, anti-inflammatory, and spasmolytic properties. Traditionally, iodimetric methods have been recommended for the quantitative determination of dipyrone in all its pharmaceutical forms. This work describes the development of zero order and fourth order (Delta lambda = 10) derivative spectrophotometric methods for the determination of dipyrone in different pharmaceutical formulations, using water as solvent. The analytical curves presented correlation coefficients greater than 0.999, limits of detection varying from 0.23 to 0.49 mg L-1, and limits of quantification varying from 0.78 to 1.63 mg L-1. The average recoveries ranged from 98 to 103 % for the zero order method and from 96 to 104 % for third and fourth order derivative methods. Intra and inter-day precisions, expressed as relative standard deviations, were below 4.2 %. The excipients present in dipyrone tablets and solutions did not interfere in the analyses. The method was shown to be linear, reproducible, specific, sensitive and rugged.
Keywords: Dipyrone; derivative Spectrophotometry; Validation; Pharmaceutical formulations